Utility of the Intradermal Skin Test in a Test-and-Cull Approach to Control Bovine Tuberculosis: A Pilot Study in Ethiopia - Lakew, Matios; Srinivasan, Sreenidhi; Mesele, Beruhtesfa; Olani, Abebe; Koran, Tafesse; Tadesse, Biniam; Mekonnen, Getnet Abie; Almaw, Gizat; Sahlu, Temertu; Seyoum, Bekele; Beyecha, Kebede; Gumi, Balako; et al. (Frontiers in Veterinary Science, 2022)
Bovine tuberculosis (bTB) is one of the top three high priority livestock diseases in Ethiopia and hence, the need for evaluation of potential control strategies is critical. Here, we applied the test-and-segregate followed by cull strategy for the control of bTB in the intensive Alage dairy farm in Ethiopia. All cattle reared on this farm were repeatedly skin tested using the Comparative Cervical Tuberculin (CCT) test for a total of five times between 2015 and 2021. During the first (October 2015) and second (March 2017) rounds of testing, all reactor animals (> 4 mm) were culled, while those that were deemed as inconclusive (1-4 mm) were segregated and retested. At retest, animals with CCT > 2 mm were removed from the herd. In the third (December 2017), and fourth (June 2018) rounds of tuberculin testing, a more stringent approach was taken wherein all reactors per the severe mode of CCT test interpretation (>2 mm) were culled. A final herd status check was performed in May 2021. During this time, the number of CCT positives (> 4mm) in the farm dropped rapidly from 23.1% (31/134) in October 2015 to 0% in December 2017 and remained 0% until May 2021. In contrast, the number of Single Cervical Tuberculin (SCT) test positives (>4 mm) increased from 1.8% to 9.5% (from 2017-2021), indicating that CCT might not be sufficient to effectively clear the herd of bTB. However, a more stringent approach would result in a drastic increase in numbers of false positives. The total cost of the bTB control effort in this farm holding 134 - 200 cattle at any given time was conservatively estimated to be approximately USD 48,000. This, together with the need for culling an unacceptably high number of animals based on skin test status makes the test-and-cull strategy impractical for nationwide implementation in Ethiopia and other low- and middle-income countries (LMICs) where the infection is endemic. Hence, there is an increased emphasis on the need to explore alternate affordable measures such as vaccination alongside accurate diagnostics to help control bTB in endemic settings.